A novel function of IL-2: Chemokine/chemoattractant/retention receptor genes induction in Th subsets for skin and lung inflammation - Sharma, Rahul; Sung, Sun-Sang J.; Gaskin, Felicia; Fu, Shu Man; Ju, Shyr-Te (Journal of autoimmunity, 2012)
The Foxp3+CD4+ regulatory T-cell (Treg)-deficient Scurfy (Sf) mice rapidly develop severe inflammation in the skin and lungs with expanded Th subsets bearing increased expression of various chemokine/chemoattractant/retention receptor genes (CRG). Nine different double mutants were generated to elucidate their roles in the skin and lung inflammation. The expanded Th2 response and the increased expression of several CRG for the skin and lung inflammation were inhibited in Sf.Il2−/− mice as previously described using microarray analysis. Herein in a reciprocal approach, we demonstrated that Sf.Il4−/− and Sf.Stat6−/− mice, despite lacking Th2 cytokines IL-4, IL-5, and IL-13, as well as the IL-4/STAT6-dependent CRG expression, the inflammation in the skin and lungs remained. The effect of the other Th1 cytokine IFN-γ was studied in Sf.Ifng−/− mice in which the multi-organ inflammation (MOI) was delayed but fully developed afterward with enhanced CRG expression except for the IFN-γ-dependent Cxcr3 in CD4+ T-cells. Similarly, a transient delay of MOI was observed for Sf.Itgae−/− mice but their Th subsets and the critical CRG expansion remained. Ltb4r1−/−, Alox5−/−, Cx3cr1gfp/gfp, or Il10−/− mutant genes also failed to effectively block inflammation in the skin and lungs in Sf mice. Our study has identified a novel function of IL-2 as a powerful Th1 cytokine that induces a panel of CRG in Th subsets required for skin and lung inflammation in Sf mice. The CRG panel induced by IL-2 but not by IL-4 or IFN-γ explains the apparent “organ-specific” display of the skin and lung inflammation in Sf mice. ► IL-2 induces trafficking related genes in Sf Th cells for skin and lung inflammation. ► Sf.Il4−/− and Sf.Stat6−/− mice develop skin and lung inflammation. ► Sf.Ifng−/− mice develop MOI without inhibition of IL-2 controlled trafficking genes. ► IL-2 has a newly identified function for Sf Th cell trafficking to skin and lungs.